Preparation and relaxation dynamics of ethylene–propylene–diene rubber/clay nanocomposites with crosslinking interfacial design. Issue 1 (31st August 2017) - Zhang, Fengshun; Zhao, Qi; Liu, Tao; Lei, Yajie; Chen, Chao
ABSTRACT: Ethylene–propylene–diene rubber (EPDM)/clay nanocomposites with crosslinking bonding at the interface were fabricated through the intercalation method involving double‐bond functional groups. For comparison, an organoclay modified with an intercalation agent without double bonds was also prepared. X‐ray diffraction indicated that the EPDM intercalated into the galleries of the nanoclay due to crosslinking with the organic intercalation reagent containing double bonds. According to the dielectric relaxation spectra, the segmental relaxation of EPDM was greatly confined, due to the strong filler/polymer interfacial interaction. And a new relaxation appeared at higher temperature and lower frequency than segmental relaxation when the content of clay with double bonds reached 10 phr; the new relaxation is attributed to interfacial relaxation. Whereas the new relaxation did not appear by adding ordinary organoclay, the dynamic mechanical analysis loss peak of EPDM, corresponding to the glass transition, moved to a higher temperature due to covulcanization. The presence of crosslinking in the EPDM/clay nanocomposites can play a significant role in improving their mechanical properties. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45553. Abstract :